Effects of Financial Development and Institutional Quality on the Economic Growth in The Arabian Gulf states: A Panel Cointegration Analysis - Yahyaoui, Abdelkarim; Al Saggaf, Majid Ibrahim (International Journal of Economics and Financial Issues, 2019)
Many studies on the link between finance and growth, in Arab gulf countries, have suggested however, without demonstrating it, that the relationship between the two spheres goes through the country’s specific institutional structure. Nevertheless, this relation is neither well analyzed nor stated in the case of the Gulf States, which justifies the problem of this article. Different estimates were made by the method of panel data for the period from 1995 to 2012 for six Arab Gulf Countries. It appears from these estimates that the quality of the institutions is the transmission vector of the financial sphere towards the real sphere for the case of these countries. So, the financial system cannot stimulate economic growth if it is accompanied by a “solid institutional framework” presented by a better bureaucracy, a fight against corruption, a strong legal framework and better socio-economic conditions. Keywords: Financial Development, Quality of Institutions, Economic Growth, Panel Data JEL Classification: O16, O43, O47, C23 DOI: https://doi.org/10.32479/ijefi.7293